Does Emotional Intelligence at medical school admission predict future licensing examination performance? - Wood, Tim J.; Humphrey-Murto, Susan; Moineau, Genevieve; Forgie, Melissa; Puddester, Derek; Leddy, John J. (Canadian Medical Education Journal, 2020)
Background: Medical school admissions committees are seeking alternatives to traditional academic measures when selecting students; one potential measure being emotional intelligence (EI). If EI is to be used as an admissions criterion, it should predict future performance. The purpose of this study is to determine if EI scores at admissions predicts performance on a medical licensure examination Methods: All medical school applicants to the University of Ottawa in 2006 and 2007 were invited to complete the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT v2.0) after their interview. Students were tracked through medical school into licensure and EI scores were correlated to their scores on the Medical Council of Canada Qualifying Examination (MCCQE) attempted between 2010 and 2014. Results: The correlation between the MSCEIT and the MCCQE Part I was r (200) = .01 p =. 90 The covariates of age and gender accounted for a significant amount of variance in MCCQE Part I scores (R2 = .10, p <.001, n=202) but the addition of the MSCEIT scores was not statistically significant (R2 change = .002, p=.56). The correlation between the MSCEIT and the MCCQE Part II was r(197) = .06, p = .41. The covariates of age and gender accounted for some variance in MCCQE Part II scores (R2 = .05, p = .007, n=199) but the addition of the MSCEIT did not (R2 change = .002 p =.55). Conclusion: The low correlations between EI and licensure scores replicates other studies that have found weak correlations between EI scores and tests administered at admissions and during medical school. These results suggest caution if one were to use EI as part of their admissions process.